Avaliação do fosfito de potássio sobre o progresso de phakopsora pachyrhizi em soja - Meneghetti, Rosana Ceolin (2009)
The effectiveness of defense activation in different soybean cultivars against Phakopsora pachyrhizi promoted by phosphite, as well as its association with fungicides in different timing application in relation to pathogen inoculation, was studied in greenhouse conditions in two trials carried out in completely randomized design, with four replications. The results showed that phosphite was unable to induce defense, because it was not observed any reduction on severity, pustules.cm-2 number, and Area Under Progress Disease Curve (AUPDC) by application of the product. The progress disease was slower in the cultivar Fundacep 55, which had a AUPDC 53% lower than cultivar Fundacep 56, the more susceptible cultivar. The fungicide epoxiconazole + pyraclostrobin reduced in almost 29% the AUPDC value when compared to isolated triazol use, considering the timing application average. The applications nearer to inoculation and the preventive fungicide applications were more effective than those applications done earlier or later in relation to plant infection by the pathogen. The data found suggest that phosphite does not induce resistance in soybean against P. pachyrhizi, but they demonstrate that there is variation on partial resistance of cultivars and on the effectiveness of fungicides between themselves and in relation to timing application of them. The Asian rust has been a great concern, due to its big potential damage and to the limited availability of control measures. This work evaluated the effect of potassium phosphite (PP) isolated and combined with epoxiconazole + pyraclostrobin, in two soybean cultivars and different fertilization levels, under Asian rust control, defoliate, yield components and grain yield. One or two PP applications were done, combined or not to fungicide (R1 and R1 + R3). Higher area under progress disease curve (AUPDC) and defoliate values were observed in the cultivar Coodetec 219 in relation to MSoy 8000. PP promoted average reduction of 9% in AUPDC and did not influence the defoliate. The AUPDC of control plot of cultivar MSoy 8000 without fertilization was 2.4-fold increased compared to 65 kg.ha-1 de P2O5 + 105 kg.ha-1 de K2O supply. The pods number, thousand grain weight and grain yield were not affected by PP. The cultivars presented difference on grain yield according to fertilizer level. The cultivar MSoy was more responsive to P nutrition, whereas on the cultivar Coodetec 219 the higher effect was due to K fertilization.